2017
DOI: 10.1002/gsj.1160
|View full text |Cite
|
Sign up to set email alerts
|

Performance Impact of Temporal Strategic Fit:Entrainment of Internationalization with Pro‐Market Reforms

Abstract: Research summary Pro‐market reforms in emerging markets evolve in a temporal pattern, however extant studies examining the impact of pro‐market reforms have eschewed temporality. We propose that the net impact of reforms on firm performance is contingent on the temporal strategic fit of the firm's strategic choice with the external environment. Using internationalization as the strategic choice, we posit that a positive impact of internationalization is contingent on whether or not firms entrain (synchronize) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 116 publications
(210 reference statements)
0
23
0
5
Order By: Relevance
“…Indian governments also started liberalizing its policies on trade and FDI in 1991. Competitive pressures on Indian firms post liberalization led to increased FDI (Popli, Akbar, Kumar, & Gaur, 2017). To promote FDI by domestic firms, Indian governments have relaxed a number of FDI policies (Popli & Sinha, 2014).…”
Section: Literature Review and Theory Developmentmentioning
confidence: 99%
“…Indian governments also started liberalizing its policies on trade and FDI in 1991. Competitive pressures on Indian firms post liberalization led to increased FDI (Popli, Akbar, Kumar, & Gaur, 2017). To promote FDI by domestic firms, Indian governments have relaxed a number of FDI policies (Popli & Sinha, 2014).…”
Section: Literature Review and Theory Developmentmentioning
confidence: 99%
“…El proceso de vigilancia tecnológica también depende de los resultados del mercado internacional y del ajuste estratégico temporal de las empresas con el entorno externo; se trata de un proceso de sincronización temporal de los parámetros de internacionalización como una estrategia de adaptación a las dinámicas globales (Popli et al, 2017). En este sentido, Pérez (2020), mediante un análisis panel con efectos temporales encuentra que las importaciones de insumos tecnológicos y de productos de alta complejidad constituyen un factor que impulsa la capacidad tecnológica en México, lo que valida la idea de que los componentes mediadores preparan el escenario propicio para explorar los canales que permiten acumular efectivamente las capacidades tecnológicas.…”
Section: Discusión Y Reflexión Teóricaunclassified
“…The entry of new entrants also increased the competitive environment as it creates pressure on a limited amount of resources available for all firms. Recent research has observed the negative impact of such pro‐market reforms on the sustainability of superior economic profits of Indian firms (Chari & David, ; Popli, Akbar, Kumar, & Gaur, ).…”
Section: Literature Review and Proposition Developmentmentioning
confidence: 99%
“…Recent research has observed the negative impact of such pro-market reforms on the sustainability of superior economic profits of Indian firms (Chari & David, 2012;Popli, Akbar, Kumar, & Gaur, 2017).…”
Section: Role Of Inward Foreign Competitionmentioning
confidence: 99%
See 1 more Smart Citation